1985
DOI: 10.1007/bf01309838
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit antibodies against the major internal protein of a retrovirus-like particle bind to epidermal cells in psoriatic skin

Abstract: A rabbit antiserum against the major internal protein, p27, of a psoriasis associated retrovirus-like particle has been used in indirect fluorescence microscopy of biopsies from psoriatic skin. The analysis indicate expression of p27 antigen in epithelial cells in psoriatic lesions and in clinically uninvolved psoriatic skin. A reaction of the antiserum with dermal vessel walls in the lesion was also observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…wt) of pso p27 is estimated to be about 30 kDa by SDS-PAGE, which is in concordance with what we have reported for the p27 antigen from psoriatic urine (1 3). We have, on the basis of several observations concerning the presence of p27 antigen in psoriatic patients (14, 15,16,17,24), suggested that the p27 antigen may play a role in the pathogenesis of psoriasis. In the present study we demonstrate that significant amounts of pso p27 antigen and anti-pso p27 antibodies are released from psoriatic scale when incubated in an acid buffer (pH 2.6).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…wt) of pso p27 is estimated to be about 30 kDa by SDS-PAGE, which is in concordance with what we have reported for the p27 antigen from psoriatic urine (1 3). We have, on the basis of several observations concerning the presence of p27 antigen in psoriatic patients (14, 15,16,17,24), suggested that the p27 antigen may play a role in the pathogenesis of psoriasis. In the present study we demonstrate that significant amounts of pso p27 antigen and anti-pso p27 antibodies are released from psoriatic scale when incubated in an acid buffer (pH 2.6).…”
Section: Discussionmentioning
confidence: 97%
“…In a series of papers (8,12,13,14,15,16,17) we have characterized retrovirus-like particles isolated from psoriatic urine and described the presence of the major internal protein, p27, of these particles in various specimens from humans. Briefly, the protein was found in some of the blood lymphocytes (0.1-1Yo) and in some of the dermal vessels and epidermal cells of psoriatic skin, and not in corresponding specimens from healthy controls with no known cases of chronic inflammatory disorders among their first-degree relatives ( 14,17). Antibodies recognizing the p27 antigen have been demonstrated in immune complexes in serum and synovial fluid from patients with psoriasis arthritis, and considerable amounts of anti-p27 antibodies can be extracted from psoriatic scale (16).…”
mentioning
confidence: 99%
“…The high concentrations of Pso p27 specific antibodies extractable from psoriatic scale show that Pso p27 acts as an immunogen [25] , [26] , and the presence of these antibodies in complement-activating immune complexes [1] suggest that Pso p27 plays a significant role in the inflammatory reactions in the psoriatic skin lesions.…”
Section: Discussionmentioning
confidence: 99%